Assessing the Role of Public Relations as an Instrument to Promote National Security - A Case of the Ghana Armed Forces - Kpabitey-Teye, Richlove Angmorkour (UniMAC - GIJ, 2020)
The study sought to investigate the role of public relations as an instrument to promote National Security using the Ghana Armed Forces as a case study. The specific objectives include to explore the use of public relations as a communication tool of the Ghana Armed Forces; to explore the challenges associated with the implementation/use of public relations in the Ghana Armed Forces and to determine the importance of public relations to the Ghana Armed Forces. The study adopted the quantitative approach to research where 50 military officers were sampled as well as 50 civilian employees. In total, a sample size of 100 respondents were obtained. The study used descriptive, explanatory and cross sectional research designs. The instrument used for data gathering is a well-structured questionnaire. The questionnaire was mainly closed ended and it helped for consistent coding and analysis with the help of IBM SPSS (version, 20). Mainly descriptive analysis was conducted to analyze the objectives of the study. Results showed that the channels of communicating with the public by the Ghana Armed Forces mostly include press releases. Finally the study concluded that public relations is important to the Ghana Armed Forces. Military officers indicated that Public relations is significant in enhancing a positive image of the military. Civilian employees however indicated that one challenge of military public relation officers is that they are not experts.
THESIS